What caused the financial crisis - Friedman, Jeff (Jeffrey); Posner, Richard A. (EBL-Schweitzer, 2011)
Featuring essays by Nobel laureate economists and an afterword by Richard Posner, this volume provides a comprehensive overview of the collapse of the global financial sector in 2008. It will be essential reading for anyone interested in the nature of modern capitalism and regulation.